The Effect of Some Toxic Anthropogenic Pollutants on Fish (Comprehensive Journal of Science, 2025)
In conclusion, the presence of ammonium nitrate in the aquatic environment can cause genetic and carcinogenic effects on fish, Therefore, it is necessary to take strict preventive measures and hold accountable and punish anyone who dares to harm the general environment, especially the marine environment, and try to educate all segments of humanity about the need to avoid dumping pollutants into the aquatic environment. The difference here is The difference between it and the terrestrial environment is that waste on land can be easily collected, cleaned, or disposed of, while in the marine environment it is extremely difficult to do so, whether through the human, material, or time-consuming efforts it requires the decline of forest areas, soil depletion, insufficient water resources, and the deterioration of fisheries are factors that threaten the quality of life and health of developing countries and make them more vulnerable to disasters, not to mention the organic pollution that occurs in fresh river water and all of it is inorganic and is not in the interest of the people living around these water sources, from which they live off their products for themselves and others, from various crops, whether plant or animal, therefore,i continue to repeat and reiterate that it is necessary to during scientific forums, we encourage the relevant decision-makers to put in place controls that would stop any reckless person who deliberately pollutes the environment, disregarding the interests of others in his community for the sake of his own interests and benefits personality, as well as individuals who dump their waste and filth into flowing rivers that carry everything deposited in them and distribute it to distant areas unaware of the toxins and dangers they contain for humans, the animal and plant worlds, and all living things.
Keywords: Waste – Pollutants – Pesticides – Poisoning – Marine Environment – Freshwater